PROJECT BASE LEARNING (PjBL) MODEL IN BIOLOGY LEARNING CONCEPT: A META-ANALYSIS - Maria Magdalena Melina; Meita Valentina Zuhro; Nurhasanah Siregar; Ristanto Ristanto; Hanum Isfaeni (Universitas Lancang Kuning, 2023)
The need for active and innovative learning models in the 21st century encourages teachers to use appropriate learning models to achieve learning objectives. PjBL is a learning model that organizes classes in a project. The purpose of this study was to re-analyze research on project-based learning models (PjBL) in biology learning. This study uses the method of meta-analysis by reviewing a number of research results related to the research theme. The samples taken from this study were 10 articles with national and international standards. Based on the results of the analysis, the overall average effect size is 0.936. This shows that overall the project-based learning model has a high effect, so that it can be used as an alternative learning model that is effectively applied in biology learning.